2004
DOI: 10.1159/000079191
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 Allele Differently Affects the Patterns of Neuropsychological Presentation in Early- and Late-Onset Alzheimer’s Disease Patients

Abstract: The presence of the apolipoprotein E (APOE) Ε4 allele is a definite risk factor for the onset of Alzheimer’s disease (AD). Its presence seems to affect especially the memory in the early stage of the disease, but the effect on the progression of the disease and survival is still controversial. Some longitudinal studies could be influenced by variables other than APOE, such as the response to medical treatment, rehabilitation therapy and inclusion of patients at different stages of progression at baseline. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 29 publications
8
39
0
1
Order By: Relevance
“…In AD patients, this finding agrees with the available literature, showing an inconsistent effect of apoE genotype on clinical severity at presentation (30,31). The majority of longitudinal studies, although, have shown that 4 is associated with more rapid cognitive decline in AD (4).…”
Section: Discussionsupporting
confidence: 89%
“…In AD patients, this finding agrees with the available literature, showing an inconsistent effect of apoE genotype on clinical severity at presentation (30,31). The majority of longitudinal studies, although, have shown that 4 is associated with more rapid cognitive decline in AD (4).…”
Section: Discussionsupporting
confidence: 89%
“…The present findings echo threads of some of the extant literature. Several studies have reported that ε4 carriers display poorer episodic memory (24)(25)(26)(27) and smaller hippocampal or other MTL volumes (17-21, 33) than noncarriers. Within the present CSF-restricted sample in which carriers and noncarriers were well matched for age and mild disease severity, we observed similar findings.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the most consistent finding is the presence of greater impairment of delayed recall on episodic memory tasks in ε4 carriers relative to noncarriers (24)(25)(26)(27), although, again, conflicting results have been reported (17,18). Findings are inconsistent regarding whether there are domains of greater cognitive impairment in noncarriers relative to carriers, with some indication that noncarriers may display greater difficulty on tasks of attention, executive, or verbal functions (17,25,26).…”
mentioning
confidence: 99%
“…Given its role in disease onset (3), the apolipoprotein E (APOE) ε4 allele may contribute to differential rates of cognitive decline in AD; however, this hypothesis has been explored for over ten years with no resolution. ε4 carriers have been found to demonstrate both slower (4)(5)(6) and faster rates of decline (7)(8)(9)(10)(11)(12)(13), potentially reflecting methodological differences in recruitment techniques, the measurement of cognition, followup time, and participants' stage of dementia. A subset of studies has also demonstrated nondifferential rates of decline in relation to ε4 status (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24); however, most of these studies had relatively small sample sizes which may have limited their ability to detect differential change over time.…”
Section: Introductionmentioning
confidence: 99%